URODYNAMIC EFFECTS OF BETA-ADRENOBLOCKERS: NEBIVOLOL ADVANTAGES - M. P. Savenkov (Racionalʹnaâ Farmakoterapiâ v Kardiologii, 2016)
Aim. To compare urodynamic effects of beta-blockers with different selectivity (propranolol, metoprolol, nebivolol) in patients with arterial hypertension (HT) and concomitant benign prostatic hyperplasia (BPH).Material and methods. 32 patients (aged 67,5 y.o. in average) with HT of 1-2 stages were involved in the study. All patients had BPH (prostate volume >40 sm3 , increase of residual urine volume) with moderate or severe low urinary tract symptoms (IPSS 8-25) and reduction of maximum urine flow rate to 5-13 ml/s. The urodynamic effect of beta-blockers was estimated by changes of urination frequency and uroflowmetry indices after single taking and 14-day therapy.Results. Propranolol and metoprolol led to aggravation of urination disorders. Nebivolol resulted in soft urodilating and urostimulating effects. It led to urination improvement and reduced a risk of urodynamic disorders.Conclusion. Urodynamic effects of cardiovascular drugs should be considered by practitioners especially in treatment of elderly patients.